Analisis Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Produk Pembalut Herbal Merek Fc Pada Konsumen Wilayah Karanganyar - Pujiani, Dewi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2014)
With the rapid development of technology, the sanitary napkins are also not least with other products. Because the pads are human needs, both women and men. Because in this study discusses the decision in purchasing consumer product brand herbal pads fc. The Data used are the primary data obtained from 100 respondents who had used the herbal pads brand products fc. The Data obtained were analyzed by using multiple linear regression analysis. The population of this research is the herbal pads brand fc customers in 2012 until 2013 as much as 200 people. The sample of this research as much as 100 respondents which is the herbal pads brand products customers fc. With the technique of sampling, simple random sampling. This research uses a multiple regression analysis with likert scale.The results showed that the marketing mix of product, price, place, and promotion of the simultaneous effect on purchasing decisions. Some of the marketing mix that most of its influence on purchasing decisions is price.Keyword : marketing mix, product, promotion, price, purchase decisions